Spontaneous Closure of a Macular Hole in Macular Telangiectasia Type 2. (May 2021) - Chandra, Varun; Merani, Rohan; Hunyor, Alex P.; Gillies, Mark
Purpose: Spontaneous closure of a macular hole in macular telangiectasia type 2 (MacTel) with vision improvement is described. Methods: A case report is presented. Results: A 71-year-old man presented with a 1-week history of distorted vision in his left eye. Left visual acuity (LVA) was 20/80. Optical coherence tomography showed an almost full-thickness left macular hole with an intact internal limiting membrane drape. Small inner retinal cavitations were present at the right macula; multimodal imaging confirmed MacTel. Managed conservatively, at 5 months the patient's LVA had improved to 20/60, the defect was no longer full thickness, and the external limiting membrane had reconstituted. At the right macula, the inner cavitations grew and outer cavitations developed, but the external limiting membrane remained intact. At 32 months, right VA was 20/20 and LVA was 20/40. Conclusions: This case of MacTel with spontaneous closure of a macular hole was associated with an overlying internal limiting membrane drape.